2004
DOI: 10.1073/pnas.0408168101
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of nucleoside triphosphates and role of the entry site to the RNA polymerase II active center

Abstract: Nucleoside triphosphates (NTPs) diffuse to the active center of RNA polymerase II through a funnel-shaped opening that narrows to a negatively charged pore. Computer simulation shows that the funnel and pore reduce the rate of diffusion by a factor of Ϸ2 ؋ 10 ؊7 . The resulting limitation on the rate of RNA synthesis under conditions of low NTP concentration may be overcome by NTP binding to an entry site adjacent to the active center. Binding to the entry site greatly enhances the lifetime of an NTP in the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
97
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 15 publications
4
97
0
Order By: Relevance
“…Our previous simulation study has suggested that the PPi release is rapid [at ∼1 μs (9)]. NTP loading has been suggested to occur in a few milliseconds (45), whereas the existence of a prebinding site may further accelerate this process. In the current study, we show that translocation can occur at timescales of tens of microseconds, which is relatively fast compared with the elongation rate (∼100 ms per base pair in vivo).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous simulation study has suggested that the PPi release is rapid [at ∼1 μs (9)]. NTP loading has been suggested to occur in a few milliseconds (45), whereas the existence of a prebinding site may further accelerate this process. In the current study, we show that translocation can occur at timescales of tens of microseconds, which is relatively fast compared with the elongation rate (∼100 ms per base pair in vivo).…”
Section: Discussionmentioning
confidence: 99%
“…NTPs have been observed bound in the catalytic site and secondary channel, but not in the main channel, and there is no obvious path for NTPs to move from the main channel to the active site (18)(19)(20)(21)(22)(23). These observations have led to the proposal that the secondary channel is the major, and perhaps only, pathway for NTPs to enter the active site (24)(25)(26)(27). Biochemical studies, however, indicate that there may be NTP binding site (s) located in the main channel of RNAP (10,16,17).…”
mentioning
confidence: 95%
“…5B), thereby changing the surrounding structure and potentially creating a looser configuration in the tunnel around the small pore that separates the E and PS sites. In addition, removal of the charged ␤Asp 675 residue will reduce the negative electrostatic potential of this pore (13).…”
Section: Table 1 Rates Of Misincorporation For Variant and Wild-type mentioning
confidence: 99%
“…High resolution structures of multisubunit RNA polymerases (RNAPs) 4 have offered insight into many of the regulatory stages and conformational changes associated with the transcription cycle (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Multiple structures of both prokaryotic and eukaryotic RNAPs have revealed a funnel-shaped pore (termed the secondary channel) leading from the surface of the enzyme directly to the active site.…”
mentioning
confidence: 99%
See 1 more Smart Citation